Retrospective analysis on efficacy of convalescent plasma in acute respiratory distress syndrome due to COVID-19 - Eren, Esma; Kılıç, Ayşegül Ulu; Korkmaz, Serdal; Yıldız, Merve; Yüksel, Recep Civan; Toker, Ayşin Kılınç; Fırat, Emine Arman; Dursun, Zehra Bestepe; Çelik, Ilhami (São Paulo Medical Journal, 2022)
BACKGROUND: Coronavirus disease 2019 (COVID-19) is an ongoing global health threat. However, currently, no standard therapy has been approved for the disease. OBJECTIVES: To evaluate the clinical effectiveness of convalescent plasma (CP) in patients with acute respiratory distress syndrome (ARDS) due to COVID-19. DESIGN AND SETTING: Retrospective study conducted at Kayseri City Education and Research Hospital, Kayseri, Turkey. METHODS: The case group consisted of adult patients (> 18 years) with ARDS due to COVID-19 who received CP in combination with antiviral and supportive treatment. These patients were compared with others who only received antiviral and supportive treatment. RESULTS: During the study period, a total of 30 patients with ARDS due to COVID-19 were included. Eleven patients (36%) received CP in combination with antiviral and supportive treatment, whereas nineteen patients (64%) in the control group only received antiviral and supportive treatment. On admission, the median age, demographic and clinical data and initial laboratory test results were similar between the groups (P > 0.05). On the 14th day of treatment, the laboratory values remained similar between the groups (P > 0.05). The mortality rates were not significantly different between the groups. CONCLUSION: CP treatment did not affect mortality or lead to clinical improvement for COVID-19 patients with ARDS.